The relationship between nightmares and depression in adolescents: the effect of age and anxiety - Li, Yuhang; Duan, Xiaorong; Han, Le; Liu, Ning; Han, Xueyang; Su, Mingzhu; Yang, Tao; He, Sha; Liu, Rui; Gao, Xinyu; Xie, Yutong; Jiang, Jie; et al. (Frontiers in Psychiatry, 2025)
IntroductionNightmares and depression are prevalent issues among adolescents. This study explores the relationship between nightmares and depression, focusing on the mediating role of anxiety and the moderating effect of ageMethodsA total of 210 adolescents aged 13 to 24 were surveyed using the Nightmare Distress Questionnaire (NDQ-CV), Self-Rating Anxiety Scale (SAS), and Self-Rating Depression Scale (SDS). They also underwent niacin skin flushing response (NSFR) testing to explore physiological correlations. A moderated mediation model was applied to assess the relationships between nightmares, anxiety, and depression. Spearman correlation analysis was used to analyze the relationship between nightmares and NSFRResultsNightmares did not directly lead to depression, but anxiety served as a full mediator in this relationship. Age had no significant moderating effect. Additionally, a significant negative correlation between nightmares and NSFR was observedConclusionNightmares contribute to anxiety, which can lead to depression in adolescents, suggesting that clinicians can identify and intervene with nightmares in adolescents to minimize the onset of psychological disorders. The study also highlights a possible connection between nightmares and NSFR, suggesting further research is needed to understand the physiological mechanisms